2022
DOI: 10.1536/ihj.21-485
|View full text |Cite
|
Sign up to set email alerts
|

Admission Hyperglycemia in Acute Type A Aortic Dissection Predicts for a Prolonged Duration of Mechanical Ventilation

Abstract: Previous studies have demonstrated that admission hyperglycemia is a predictor of mortality and poor prognosis in patients with cardiovascular diseases, such as acute myocardial infarction. However, the prognostic value of admission hyperglycemia in patients with acute type A aortic dissection (AAAD) has never been explored. To clarify the association between hyperglycemia and in-hospital outcomes, we retrospectively analyzed 734 patients with AAAD. The interest endpoints were in-hospital mortality rate, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Lin et al. indicated that there was a strong correlation between admission hyperglycemia and postoperative mechanical ventilation time ( 29 ). However, there is few studies that focus on the relationship between PHG and outcomes of patients with TAAD who underwent open chest surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al. indicated that there was a strong correlation between admission hyperglycemia and postoperative mechanical ventilation time ( 29 ). However, there is few studies that focus on the relationship between PHG and outcomes of patients with TAAD who underwent open chest surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al. suggested that admission blood glucose level was not associated with in-hospital mortality of patients underwent surgery for TAAD ( 29 ). However, there is few studies explore the relationship between PHG and in-hospital mortality of patients under surgery for TAAD.…”
Section: Discussionmentioning
confidence: 99%